Baliwag Navigation, Inc. - Velasco, Emmanuel Quintos (Animo Repository, 1999)
Baliwag Navigation, Inc. (BNI) is a 100% Filipino-owned corporation who is one of the major players in the manpower services industry in the country. The manpower services industry satisfies the need for human resources (workers) by employers either for land-based or sea-based deployment. An analysis of the industry and the company was made to arrive at the most appropriate corporate strategies, and to establish the best means of achieving them.